Neovascular Prostate-Specific Membrane Antigen Expression Is Associated with Improved Overall Survival under Palliative Chemotherapy in Patients with Pancreatic Ductal Adenocarcinoma. (25th October 2017) - Stock, Katharina; Steinestel, Konrad; Wiesch, Rebekka; Mikesch, Jan-Henrik; Hansmeier, Anna; Trautmann, Marcel; Beller, Nora; Rehkämper, Jan; Wardelmann, Eva; Heitkötter, Birthe; Hartmann, Wolfgang; Sperveslage, Jan; et al.
Abstract : Aims . Expression of PSMA (prostate-specific membrane antigen) has been demonstrated in various cancers, including pancreatic ductal adenocarcinoma (PDAC). However, PSMA expression in PDAC-associated neovasculature has so far not been systematically analyzed. Methods and Results . We analyzed PSMA expression in 81 PDAC tissue samples from 61 patients. Microvessel density (MVD) was assessed by software-based image analysis and showed a mean MVD of 63.7 microvessels/0.785 mm 2 . PSMA was practically absent in tumor tissue (5.3%) and PDAC cell lines (0/7) but could be detected in tumor-associated neovasculature in 53.2% of cases. There was no association between neovascular PSMA expression and clinicopathological tumor characteristics. Samples with PSMA+ neovasculature showed increased MVD; however, this result was not statistically significant (p > 0.05 ). Presence of PSMA+ neovessels correlated with overall survival under palliative chemotherapy (894 versus 400 days; HR 0.42; 95% CI: 0.12 to 0.87; p < 0.05 ). Conclusion . PSMA expression in tumor-associated neovasculature is a common feature and associated with improved overall survival under palliative chemotherapy in PDAC. Our results point towards a possible association between PSMA expression and response to therapy which might be based on enhanced intratumoral bioavailability of systemic chemotherapy.